2024
DOI: 10.3389/fphar.2024.1309178
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin: what is the in vitro evidence for its antitumor potential and beyond?

Jiaming Lei,
Jianbao Yang,
Cuiyu Bao
et al.

Abstract: Isorhamnetin (ISO) is a phenolic compound belonging to flavonoid family, showcasing important in vitro pharmacological activities such as antitumor, anti-inflammation, and organ protection. ISO is predominantly extracted from Hippophae rhamnoides L. This plant is well-known in China and abroad because of its “medicinal and food homologous” characteristics. As a noteworthy natural drug candidate, ISO has received considerable attention in recent years owing to its low cost, wide availability, high efficacy, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
0
0
0
Order By: Relevance
“…Isorhamnetin (ISO, C 16 H 12 O 7 , Fig. 1 A) is a type of flavonoid compound that occurs in various types of plants, such as Hippophae rhamnoides L and Ginkgo biloba L. A previous study showed that ISO exhibits several biological activities, including anti-inflammatory, antioxidant, antitumor activity, and antifibrosis [ 9 , 10 ]. Liu et al reported that ISO suppresses liver fibrosis by decreasing ECM deposition via TGF-β1/Smad3 and TGF-β1/p38 MAPK pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isorhamnetin (ISO, C 16 H 12 O 7 , Fig. 1 A) is a type of flavonoid compound that occurs in various types of plants, such as Hippophae rhamnoides L and Ginkgo biloba L. A previous study showed that ISO exhibits several biological activities, including anti-inflammatory, antioxidant, antitumor activity, and antifibrosis [ 9 , 10 ]. Liu et al reported that ISO suppresses liver fibrosis by decreasing ECM deposition via TGF-β1/Smad3 and TGF-β1/p38 MAPK pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%